2018
DOI: 10.1136/jclinpath-2018-205095
|View full text |Cite
|
Sign up to set email alerts
|

Smad4/DPC4

Abstract: Smad4 or DPC4 belongs to a family of signal transduction proteins that are phosphorylated and activated by transmembrane serine-threonine receptor kinases in response to transforming growth factor beta (TGF-β) signaling via several pathways. The gene acts as a tumour suppressor gene and inactivation of smad4/DPC4 is best recognised in pancreatic cancer. However, smad4/DPC4 is also mutated in other conditions and cancers such as juvenile polyposis sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…However, in advanced tumors with high expression, TGF-β stimulates carcinogenesis and metastasis[12-14]. Furthermore, increased TGF-β expression inactivates the tumor suppressor gene Smad4/DPC4, the loss of which is commonly implicated in PC tumor progression[15,16]. TGF-β is also considered to be a negative regulator of skeletal muscle via the Smad2/3 pathway, which contributes to myopenia via myostatin, activin and inhibin signaling[17].…”
Section: Pancreatic Cancer Induced Cachexiamentioning
confidence: 99%
“…However, in advanced tumors with high expression, TGF-β stimulates carcinogenesis and metastasis[12-14]. Furthermore, increased TGF-β expression inactivates the tumor suppressor gene Smad4/DPC4, the loss of which is commonly implicated in PC tumor progression[15,16]. TGF-β is also considered to be a negative regulator of skeletal muscle via the Smad2/3 pathway, which contributes to myopenia via myostatin, activin and inhibin signaling[17].…”
Section: Pancreatic Cancer Induced Cachexiamentioning
confidence: 99%
“…Studies have found that Smad4 is closely related to cell proliferation and apoptosis (15)(16)(17). It has been found in tumor research that Smad4 is a tumor suppressor gene, and its decreased or absent expression in a variety of tumors has been found to lead to the abnormal proliferation of tissues and cells (19,20); however, it has been found in some studies of cardiovascular diseases that TGF-β1/Smad4 can inhibit cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the classical TGF-β pathway, activated Smad2/3 and Smad4 form the SMAD complex, which translocates to the nucleus (14). Smad4 is considered to be a tumor suppressor gene that is closely related to cell apoptosis (15)(16)(17). Imbalance of Smad4 expression in the TGF-β signaling pathway may lead to various diseases, including cancers, fibrous lesions, metabolic diseases and cardiovascular diseases (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…TSPO and SMAD4 play an important role in steroid synthesis [ 1 , 3 ], but the current research on these two genes mainly focuses on mitochondrial function [ 14 ], oxidative stress [ 15 ] and signal transduction [ 16 ]. Several studies reported that TSPO ligand promoted pregnenolone synthesis [ 14 ], and TGF-β/SMAD4 signaling pathway regulated steroid production and ovarian development [ 17 ], but these studies are rare in fish.…”
Section: Discussionmentioning
confidence: 99%